Kualitas Hidup pada Pasien Pasca Serangan Jantung di RSU Kota Mataram Tahun 2019-2020 - seto priyambodo; Basuki Rahmat; I Putu Arya Primananda; Kadek Adi Sagita Reka Baya (Unram Medical Journal, 2022)
Background: Acute coronary syndrome is a non-communicable disease whose prevalence is increasing every year. The impact after a heart attack is a decrease in the patient's quality of life. This study aims to determine the characteristics and factors associated with the quality of life of patients after a heart attack. Methods: This research is a quantitative study with a cross sectional design. The research sample was patients after a heart attack at the Mataram General Hospital in 2019-2020. Data on smoking characteristics and status were collected through forms using a structured questionnaire, while quality of life data was collected using the SF-36 questionnaire. Results: Characteristics of post-heart attack patients at Mataram General Hospital were male (86.7%), aged <60 years (60%), smoking status (40%), STEMI diagnosis (50%), and poor quality of life. (63.6%). No significant relationship was found between gender , age , type of diagnosis and smoking status with the patient 's quality of life . Conclusion: There are 63.6% of patients with poor quality of life. There is no significant relationship between gender, smoking status, age, type of diagnosis and quality of life. Patients with smoking status tend to have a poor quality of life in the domains of physical roles (91.7%) and emotional roles (83.3%).